Khaleed Abou el Fadl's Hermeneutic: A Newly Proposed Insight to Review Ibnu Rushd’s Theory of Despotic Interpretation of The Qur’an - Muhammad Muzayyin (Universitas Islam Negeri Mataram, 2016)
This paper examines Ibn Rushd’s theory of interpretation of the Qur’an by using a new methodology of hermeneutic developed by Khaleed Abou El Fadl. He proposes a theory of ‘negotiating hermeneutic’, in his work Speaking in The God’s Name: Islamic Law, Authority, and Womans. This theory advances the role of text (the Qur’an and hadith), authors (mufti, interpreter, special agent), and readers (Muslim society, common agent) in determining the objective of an authoritative text. These are three elements that must work together to determine meanings. Abou El Fadl’s hermeneutic theory develops the idea of autonomous and open texts. Therefore, the interpretation of the text does not always focus on locating the author’s desired intent. Building on El Fadl’s theory, the study aims to review Ibn Rushd’s authoritarian interpretation, which tends to push away any other understanding which is opposite to an interpreter’s ideology. Hence, this theory is contrary to another theory which states that there are no authoritative figures who can objectively understand the Qur’an. DOI: http://dx.doi.org/10.20414/ujis.v20i1.534